Perancangan Kursi Bongkar Pasang (Knockdown) dengan Ornamen dari Limbah Ranting Kayu - Aliyyudin Erick Kurniawan; Jati Widagdo; Sutarya Sutarya (Jurnal Riset Rumpun Seni, Desain dan Media, 2025)
In the furniture packaging process, there is one problem that often hinders the effectiveness of time and space used. Many furnitures are designed in compact or intact forms so they cannot be disassembled. This affects the process of loading goods into a truck or container which is becoming increasingly limited in quantity. If the furniture is designed as knockdown, the process of loading goods will be easier and can save time, space, and energy. The knockdown furniture designed is a chair inspired by disassembly toys such as lego, figurines or action figures, and tazos. For aesthetic impression to the product, ornaments or decorations are added with materials from wood waste. Various types of wood waste found in furniture industry locations include bark, wood pieces, wood chips, and sawdust. The use of wood waste as decorative element in designed products can reduce the amount that often piles up as waste that cannot be used. This waste is even only used as burning material for other production waste causing negative impact on the environment due to air pollution. The wood waste utilized is teak wood branch waste that cut into small circles to be glued to the knockdown chair designed.